2017
DOI: 10.1038/tp.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

Two subgroups of antipsychotic-naive, first-episode schizophrenia patients identified with a Gaussian mixture model on cognition and electrophysiology

Abstract: Deficits in information processing and cognition are among the most robust findings in schizophrenia patients. Previous efforts to translate group-level deficits into clinically relevant and individualized information have, however, been non-successful, which is possibly explained by biologically different disease subgroups. We applied machine learning algorithms on measures of electrophysiology and cognition to identify potential subgroups of schizophrenia. Next, we explored subgroup differences regarding tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 44 publications
1
34
1
3
Order By: Relevance
“…In future work, there are several other mechanisms that could be tested. These include alternative late integration schemes, as well as other imputation types, such as multiple imputation and imputation with reject option 17,57 .…”
Section: Discussionmentioning
confidence: 99%
“…In future work, there are several other mechanisms that could be tested. These include alternative late integration schemes, as well as other imputation types, such as multiple imputation and imputation with reject option 17,57 .…”
Section: Discussionmentioning
confidence: 99%
“…As part of a multimodal cohort study, both in- and out-patients aged 18 to 45 years presenting with a first-episode of schizophrenia were referred from Mental Health Services in the Capital Region of Denmark from December 2008 to April 2014. The cohort was initially presented in Nielsen et al (2012) , and there is partial overlap with aspects of data presented on cortical thickness, WM and psychotic symptoms, and machine learning ( Bak et al, 2017 ; Ebdrup et al, 2016 ; Jessen et al, 2018 ), see also www.cinsr.dk for other publications from this cohort. Patients fulfilling criteria of an ICD-10 diagnosis of schizophrenia were included.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research examining treatment resistance in schizophrenia has pointed out several factors, including issues of cognitive functioning or cognitive disability in schizophrenia. 23,24 A study which conducted long-term follow-up of schizophrenia patients showed that those with the poorest response to treatment typically had higher rates of negative symptoms and worse cognitive functioning at baseline. 25 Likewise, another study recently found that measures of cognitive functioning accurately predicted treatment response to antipsychotic medication, even when there were no differences in measures of psychopathology between treatment responders and nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…25 Likewise, another study recently found that measures of cognitive functioning accurately predicted treatment response to antipsychotic medication, even when there were no differences in measures of psychopathology between treatment responders and nonresponders. 24 Given the relation between poor treatment response and cognitive functioning, it is worth noting that cognitive impairment of some form is considered a hallmark of schizophrenia. [26][27][28] Generally, in our hospitals, we have found most patients actively psychotic are stabilized with the use of antipsychotic medication early in their hospital stay.…”
Section: Discussionmentioning
confidence: 99%